Estimation of calculation (measurement) step of backscattering pattern for complex shape objects - Масловський, О. А.; Легенький, М. М.; Антюфєєва, М. С. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
In order to obtain the exact values of the detection probability of complex shape object it is necessary to obtain the RCS value for each possible observation angle that requires a lot of calculations for each object. In the paper the investigation the necessary number of measurements (or calculations) the facility RCS required for a sufficiently accurate determination of the statistical characteristics of the object visibility is provided. The results are confirmed by calculations for a number of different objects: tank model and two models of aircraft. Thus, angular mesh density requirements for the backscatter pattern to determine the RCS to obtain reliable estimates of the statistical characteristics of the object are defined